Application research on nonlinear partitioned analysis of soil-structure interaction method of seismic response for seawater-seabed-structure - Hao Lv (Scientific Reports)
Abstract The analysis of seismic response in marine engineering structures is pivotal for guaranteeing their seismic safety. Such analyses are intricate due to the complexity of fluid–structure and soil-structure interactions. This paper introduces a unified computational framework for wave motion within a water-saturated seabed-bedrock system, employing the Davidenkov model and a modified Massing rule to characterize the nonlinear properties of the saturated seabed. A comparative analysis is conducted between the nonlinear responses of marine sites subjected to linear and nonlinear free-field inputs, with a specific focus on the seismic response of bridges under seawater-seabed-structure interaction. The study demonstrates that the modulus of a nonlinear saturated seabed diminishes, leading to a decrease in the wave impedance ratio between the saturated seabed and bedrock. Consequently, the reflection and transmission coefficients from the bedrock to the saturated seabed increase, amplifying the seismic response. For deepwater bridges, under harder site conditions, the abutment’s bottom response is largely insensitive to increasing water depth, whereas the shear at the abutment’s base diminishes with increasing water depth. The proposed method is validated through two case studies, with an examination of the impact of saturated sites on the analysis results.